EXPLORING LEADERSHIP STYLES THAT INFLUENCE PROACTIVE WORK BEHAVIOR - Bella, Bella Ghia Dimmera; Ramadania (Sekolah tinggi ilmu ekonomi pemuda, 2024)
Employees proactive work behavior is essential in today's dynamic work environment. Leadership strongly influences the proactive work behavior of employees. The purpose of this systematic literature review is to investigate leadership styles that may influence employees' proactive work behavior. The methodology employed stringent inclusion and exclusion criteria to explore relevant journal articles within the Google Scholar database. The review showed that leadership styles such as servant leadership, inclusive leadership, empowering leadership, spiritual leadership, authentic leadership, entrepreneurial leadership, humble leadership, shared leadership, transformational leadership, paradoxical leadership, visionary leadership, authentic leadership, distributed leadership, and ethical leadership strongly influence proactive work behavior. These leadership styles motivate employees to take initiative, seek opportunities, and engage in other proactive work behaviors. Theory explains the influence of leadership on proactive work behavior. These results also have real consequences for organizations in terms of building leadership training programs that enable employees to be more proactive. We recommend conducting additional research on the moderating and mediating effects on the relationship between leadership and proactive work behavior.